Legal responsibility for injuries sustained on the field during sports competitions - boussag, fatiha (sports creativity, 2025)
In our time, sports are considered an important aspect of life for all peoples of the world, as they instill in the human psyche ethics that promote communication and cooperation among all, regardless of religion, race, gender, or color. Sports are no longer merely a form of entertainment or recreation to pass the time and fill leisure time; rather, governments and countries now give them great importance in the national development process, allocating huge financial resources to them, just like any other economic sector, in order to establish and construct sports facilities and infrastructure.